Impact of social support on college students’ anxiety due to COVID-19 isolation: Mediating roles of perceived risk and resilience in the postpandemic period - He, Tai Bo; Tu, Chia Ching; Bai, Xue (Frontiers in Psychology, 2022)
Introduction Because of the outbreak of COVID-19, several colleges and universities in Xi’an, China, implemented quarantine measures and closed their gates, which increased anxiety among the students. Methods The Perceived Social Support Scale, Perceived Risk of COVID-19 Pandemic Scale, Connor–Davidson Resilience Scale, and Self-Rating Anxiety Scale were used for measurements. SPSS26 and AMOS26 (IBM SPSS AMOS Statistics, New York, United States) were used for data analysis. Structural equation modeling (SEM) was used to test the data from the 2,251 respondents and the hypothetical model. Results The students’ perceived social support was discovered to have had a significant negative effect on anxiety. The students’ perceived COVID-19 risk and resilience played significant mediating roles in the relationship between social support and anxiety. Discussion When college students feel social support and have resilience, they can reduce anxiety during the epidemic stage. Therefore, education administrators and parents should help college students to identify the current situation of the epidemic environment, enrich relevant knowledge.